2011
DOI: 10.1097/inf.0b013e3181ffe3eb
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Decline in Rotavirus Detections in the United States Following the Introduction of Rotavirus Vaccine in 2006

Abstract: Rotavirus activity was substantially diminished during the 2009-2010 rotavirus season compared with the prevaccine baseline and the 2 previous postvaccine introduction seasons. These sustained declines over 3 rotavirus seasons reaffirm the health benefits of the US rotavirus vaccination program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 7 publications
7
65
0
1
Order By: Relevance
“…Similar to earlier studies 12,13 we showed that universal rotavirus immunization was followed by blunting and delaying of winter peaks of RVGE. Therefore, in settings with known and typical rotavirus seasonality, especially in high income countries, 24 blunted peaks in all-cause gastroenteritis might be used as a proxy for monitoring short-term impact of introducing rotavirus immunization.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar to earlier studies 12,13 we showed that universal rotavirus immunization was followed by blunting and delaying of winter peaks of RVGE. Therefore, in settings with known and typical rotavirus seasonality, especially in high income countries, 24 blunted peaks in all-cause gastroenteritis might be used as a proxy for monitoring short-term impact of introducing rotavirus immunization.…”
Section: Discussionsupporting
confidence: 75%
“…Clinical trials and post-marketing studies demonstrated high efficacy (81%-100%) of both vaccines in preventing severe RVGE in infants in developed countries, 9,10 and significant reduction in RVGE disease burden in settings that introduced rotavirus immunization programs. [11][12][13][14] Though the World Health Organization recommends routine rotavirus vaccination for infants worldwide, rotavirus immunization has been introduced into childhood immunization programs in only a limited number of countries. [15][16][17] Among the barriers to universal rotavirus immunization is skepticism regarding the need and potential benefit of rotavirus immunization in reducing RVGE disease burden, vaccine safety concerns, and cost issues.…”
Section: Introductionmentioning
confidence: 99%
“…8 The impact of the vaccines in reducing hospitalizations and outpatient visits in the U.S. has been substantial. [9][10][11][12][13][14][15] However, two recent findings have raised potential concerns about the safety of current rotavirus vaccines. In March 2010, the U.S Food and Drug Administration (FDA) recommended temporarily suspending use of RV1 because of the detection of porcine circovirus, a nonhuman pathogen, in the vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Two important studies published in the New England Journal of Medicine 4,5 confirmed their efficacy and safety. Since then, the two vaccines have gone into general usage and the burden of the disease and severity of diarrhoeal illnesses have been significantly and substantially reduced in several countries by the use of these vaccines 6,7,8 . The vaccines are used in the National Immunisation Programmes of several countries.…”
mentioning
confidence: 99%